Shelf-Life Study of Bleached and Raw Jute Keeping in Normal and Air Tight Conditions - Hye, M A; Khaleque, M A; Islam, M A; Akhtar, A (Journal of Bangladesh Academy of Sciences, 2012)
When the raw and bleached jute were kept in air tight and normal conditions it was found that in normal condition the tensile strength of raw jute decreased with increase of times. But in air tight condition the decreasing rate of tensile strength of both kinds of jute was approximately similar. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12973 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 263-266, 2012